Encountering tūrangawaewae and whanaungatanga : Māori, interconnection and a place to stand in Kairākau and Aroha Bridge : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Media Studies at Massey University, Manawatū, New Zealand - Williams, Kristian (Massey University, 2018)
The establishment of Māori Television, alongside the development of public funding agencies like NZ on Air, and the expansion of media consumption to include online spaces has meant that Māori media has become an increasingly significant presence in the lives of both Māori and non-Māori viewers. However, there remains relatively little research into the ways in which this media can facilitate understanding of te ao Māori. Combining elements of postcolonial theory and kaupapa Māori criticism, this thesis examines the ways in which the textual representations, production practices, and distribution methods of the webseries Aroha Bridge and the television series Kairākau shape an understanding of tūrangawaewae and whanaungatanga. The thesis shows how the textual representations within the two series construct tūrangawaewae and whanaungatanga in complementary but also contrasting ways, providing a place to stand and fostering connections that are, for example, dynamic and informed by tradition, and that value cultural hybridity and autonomy. Through analysis of the production and distribution contexts in which the series are situated, the thesis also highlights the economic, cultural, and technological factors that present opportunities or obstacles for the realisation of tūrangawaewae and whanaungatanga on and off screen. The thesis thus reveals the value of Māori media as a resource for learning about te ao Māori, the ways in which te ao Māori is evolving in the contemporary mediascape, and the structural factors upon which these developments are contingent.
Keywords: New Zealand; Māori Television; Ethnic television broadcasting; Television programs; Maori (New Zealand people); Social conditions; Social life and customs; Drama; Rārangi pouaka whakaata; Hōtaka (Pāpāho); Tūrangawaewae; Whanaungatanga